Analisis Dosis Paparan Radiasi Pada General X-Ray II Di Instalasi Radiologi Rumah Sakit Muhammadiyah Semarang - Ida Septiyanti; M. Ardhi Khalif; Edi Daenur Anwar (Jurnal Imejing Diagnostik (JImeD), 2020)
Background: This study analyzes the Radiation Dose of the General X-ray Radiology Installation at Roemani Hospital  Muhammadiyah Semarang to determine the dose received by the radiographer, the community around the room and to know the value of the effectiveness of radiation protection and to determine the pattern of radiation exposure distribution in the general X-ray radiology installation room II.Methods: Measurements were taken during general X-ray exposure and without exposure using a 451P ion chamber survey. Measurement of dose data received by the radiographer and the community around the room is taken at the point of the operator’s room, service room, waiting room. As for the measurement of the effectiveness of radiation protection taken at the point in the operator’s room and the general X-ray II and the radiation distribution pattern taken at points A, B, C, D and E with a distance of 40 cm, 80 cm and 120 cm in the room general X-ray II.Result: The result of measurements in the operator room are 0.0354 µSv / hour, waiting rooms with a distance of 3.5 m at 0.0146 µSv / hour, in the service room and waiting room with a distance of 8 m at 0 µSv / hour. The value of the effectiveness of radiation protection in the operator station is 83.33% and the general X-ray II door is 84.09%.Conclusions: Based on the results of the data obtained the value of the dose received and the value of effectiveness is quite safe from excessive radiation exposure. The radiation distribution pattern, the farther the distance from the radiation source, the measured radiation exposure value will be lower.